China, the EU and international investment law : reforming investor-state dispute settlement - Li, Yuwen, 1962-; Qi, Tong, 1972-; Bian, Cheng (Legal researcher) (London : Routledge, 2019)
This book provides an original and critical analysis of the most contentious subjects being negotiated in the China-EU Comprehensive Agreement on Investment (CAI). It focuseson the pathway of reforming investor-state dispute settlement (ISDS) from both Chinese and European perspectives in the context of the China-EU CAI and beyond. The book is divided into three parts. Part I examines key and controversial issues of the China-EU CAI negotiations, including market access, sustainable development and human rights, as well as comparing distinct features between the China-EU CAI and the China-US BIT. Part II concentrates on the institutional reform of investor-state arbitration with an extensive analysis of the EU's approach to replacing the private nature of investment arbitration with the public nature of an investment court. Part III addresses the core substantive and procedural issues concerning ISDS, such as the role of domestic courts in investment dispute settlement, the status of state-owned enterprises (SOEs) as investors, transparency and the protection of victims in investment dispute resolution. This book will be of interest to scholars and practitioners in the field of international investment and trade law, particularly investment dispute settlement.
"This book provides an original and critical analysis of the most contentious subjects being negotiated in the China-EU Comprehensive Agreement on Investment (CAI). It focuses on the pathway of reforming investor-state dispute settlement (ISDS) from both Chinese and European perspectives in the context of the China-EU CAI and beyond. The book is divided into three parts. Part I examines key and controversial issues of the China-EU CAI negotiations, including market access, sustainable development, human rights, as well as comparing distinct features between the China-EU CAI and the China-US BIT. Part II concentrates on the institutional reform of investor-state arbitration with an extensive analysis of the EU's approach to replacing the private nature of investment arbitration with the public nature of an investment court. Part III addresses the core substantive and procedural issues concerning ISDS, such as the role of domestic courts in investment dispute settlement, the status of state-owned enterprises (SOEs) as investors, transparency, and protection of victims in investment dispute resolution"--
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Business Law; LAW / General; LAW / Alternative Dispute Resolution; Investments, Foreign -- Law and legislation -- China; Investments, Foreign -- Law and legislation -- European Union countries; Investments, Foreign (International law); China -- Foreign economic relations -- European Union countries; European Union countries -- Foreign economic relations -- China